Automated and Continuous Production of Polymeric Nanoparticles - Bovone, Giovanni; Steiner, Fabian; Guzzi, Elia A.; Tibbitt, Mark W. (Frontiers in Bioengineering and Biotechnology, 2019)
Nanoparticles (NPs) are increasingly used as therapeutics, diagnostics, and building blocks in (bio)materials science. Current barriers to the translation of polymeric NPs are the limited control over and scale of their production. Flow-based devices have emerged for controlled production of polymeric NPs, both for rapid formulation screening (ug min-1) and on-scale production (mg min-1). While flow-based devices have improved NP production compared to traditional batch processes, automated processes are needed for robust NP production at scale. Therefore, we have engineered an automated coaxial jet mixer (CJM), which controlled the mixing of an organic stream containing block copolymer and an aqueous stream, for the continuous nanoprecipitation of polymeric NPS. The CJM was operated under computer control stably for up to 24 h and automated control over the flow conditions tuned poly(ethylene glycol)-block-polylactide (PEG-b-PLA) NP size between 56 nm and 79 nm. In addition to stable operation, the automated CJM enabled production of NPs of similar size (Dh = 50 nm) from chemically diverse block copolymers, PEG-b-PLA, PEG-block-poly(lactide-co-glycolide) (PEG-b-PLGA), and PEG-block-polycaprolactone (PEG-b-PCL), by tuning the flow conditions. The automated CJM was used to produce model nanotherapeutics in a reproducible manner without user intervention. Finally, NPs produced with the automated CJM were used to scale NP synthesis and the formation of injectable polymer–nanoparticle (PNP) hydrogels without modifying mechanical properties. In conclusion, the automated CJM enabled stable, tunable, and continuous production of polymeric NPs, which are needed for the scale-up and translation of this important class of biomaterials.